2015
DOI: 10.1177/1029864915598663
|View full text |Cite
|
Sign up to set email alerts
|

Estonian children’s improvisational songs, the nature of performance and songs’ coherence with the Western tonal musical canon

Abstract: In this preliminary study, improvisational songs of 43 Estonian children (22 girls, 21 boys, M age = 5.5 years, age range: 2-8 years) were collected using the AIRS Test Battery of Singing Skills (ATBSS). Improvisational songs from two tasks of the ATBSS (song completion and song creation) were evaluated by three experts according to the performance's coherence with the relevant criteria of children's songs in the Western musical canon (a song has a melody and a rhythm and ends on the tonic) and the spontaneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Singing is a universal human activity that is considered to be one of the most natural means of human expression (Lomax, 1968; Nettl, 2015). For example, children have a natural tendency to sing spontaneously early in development (Dalla Bella, Giguère, & Peretz, 2007), and several studies have sought to analyze the products of children’s vocal improvisations (e.g., Campbell, 1998; Cohen, 2011; Moog, 1976; Moorhead & Pond, 1978; Raju & Ross, 2012; Raju et al, 2015; Sundin, 1997; Young, 2002). Even though singing begins naturally as a process of vocal play during the early years of life, not all individuals continue to sing or make music after childhood (Nordoff & Robbins, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Singing is a universal human activity that is considered to be one of the most natural means of human expression (Lomax, 1968; Nettl, 2015). For example, children have a natural tendency to sing spontaneously early in development (Dalla Bella, Giguère, & Peretz, 2007), and several studies have sought to analyze the products of children’s vocal improvisations (e.g., Campbell, 1998; Cohen, 2011; Moog, 1976; Moorhead & Pond, 1978; Raju & Ross, 2012; Raju et al, 2015; Sundin, 1997; Young, 2002). Even though singing begins naturally as a process of vocal play during the early years of life, not all individuals continue to sing or make music after childhood (Nordoff & Robbins, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Another study of creativity in Estonian children of 2-8 years of age showed that their self-made songs were similar in creativity to their Canadian peers than to children in Japan (Raju et al, 2015).…”
Section: Mesotonal Mode and Divergence Of Hemitonic/anhemitonic Typesmentioning
confidence: 98%
“…As Kartomi (1991) has argued, children at play produce many improvisations that may quickly dissipate or turn into new songs. These vocal practices are a staple of early childhood (Bjørkvold, 1992; Moorhead & Pond, 1978) and are often taken as evidence of musical development (Raju, Välja, & Ross, 2015). Improvised songs are said to submerge over the course of time (Barrett, 2006; Knudsen, 2008; Young, 2006), particularly with children’s entrance into formal schooling, when “play-based provision gradually shifts in favor of a more product-oriented, skills-based approach to education” (Marsh & Young, 2016, p. 463).…”
Section: Improvisation In a Developmental Perspectivementioning
confidence: 99%
“…Two recent studies suggest that culture, context and the nature of tasks impact children’s vocal improvisations and invented songs (Adachi & Trehub, 2011; Raju, Välja, & Ross, 2015). A question that remains to be answered is whether children’s improvised songs change over the course of development, and if so, what is the nature of such changes and what influences them.…”
Section: Improvisation In a Developmental Perspectivementioning
confidence: 99%
See 1 more Smart Citation